Roma Minority Youth Across Cultural Contexts: Taking a Positive Approach to Research, Policy and Practice (Review) - Manrique Millones, Denisse Lisette (2021)
A Book Review on Roma Minority Youth Across Cultural Contexts: Taking a Positive Approach to Research, Policy and Practice Radosveta Dimitrova, David Lackland Sam, and Laura Ferrer-Wreder (Oxford University Press), 2021, 264 pages, ISBN: 9780190654061.